Effect of Accountability, Transparency and Supervision on Budget Performance - HARNOVINSAH, HARNOVINSAH; AL-HAKIM, Y.; ERLINA, ERLINA; MUDA, I. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research aims to examine the effect of accountability, transparency, and supervision on-budget performance of the Value for Money concept. The research was conducted on 43 local work units in Special Capital Region (DKI) Jakarta Province. The sample of the research consists of 86 government officials using Structural Equation Modeling (SEM) analysis to test the hypothesis. The result of this research-proven that accountability and supervision have significantly affected the on-budget performance of the Value for Money concept, while transparency showed no effect on the effectiveness on-budget performance of the same concept.RESUMEN Esta investigación tiene como objetivo examinar el efecto de la rendición de cuentas, la transparencia y la supervisión en el rendimiento presupuestario del concepto Value for Money. Investigación realizada en 43 unidades de trabajo locales en la Región de Capital Especial (DKI) Provincia de Yakarta. La muestra de la investigación consta de 86 funcionarios gubernamentales y se utiliza el análisis de modelado de ecuaciones estructurales (SEM) para probar la hipótesis. El resultado de esta investigación demostró que la rendición de cuentas y la supervisión tienen un efecto significativo en el rendimiento presupuestario del concepto Value for Money, mientras que la transparencia no mostró ningún efecto sobre la eficacia en el rendimiento presupuestario del mismo.